PENGARUH AUDIT STRUCTURE, ORGANIZATIONAL CITIZENSHIP BEHAVIOUR, TASK COMPLEXITY, DAN ROLE CONFLICT TERHADAP KINERJA AUDITOR INTERNAL DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MODERASI - Nurul Fadhilah Farid (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
The problem examined in this study is how the influence of Audit Structure,Organizational Citizenship Behavior, Task Complexity, and Role Conflict on InternalAuditor Performance. The number of previous research results that are inconsistentmakes researchers redevelop this research by adding Job Satisfaction as a moderatingvariable. The purpose of this research is to be able to analyze and find empirical evidenceof the influence of all independent variables on the dependent variable under study. Thisresearch was conducted on two State Owned Enterprises engaged in services, namely PTPos Indonesia (Persero) and PT Kereta Api Indonesia (Persero) by involving internalauditors as respondents by distributing research questionnaires. The research methods used in this study are; descriptive statistics, instrument quality test, classic assumptiontest and hypothesis test. The results obtained from this study are the variable AuditStructure and Organizational Citizenship Behavior proven to have a positive effect onInternal Auditor Performance, whereas the variable Task Complexity and Role Conflictare proven to have a negative effect on Internal Auditor Performance. Meanwhile the JobSatisfaction variable that acts as a moderating variable in this study is proven as amoderating variable that strengthens the influence of Audit Structure and OrganizationalCitizenship Behavior on Internal Auditor Performance, but on the other hand weakensthe influence of Task Complexity and Role Conflict on Internal Auditor Performance